Penguatan Nilai Karakter Qur’ani Melalui Pembelajaran Bimbingan Baca Al-Qur’an (BBQ) di MTs Al-Hikmah Bandar Lampung - Dessy Rusmia Sari; Imam Syafe’i; Ais Isti’ana; Siti Zulaikhah; Agus Faisal Asyha (CV. Creative Tugu Pena, 2024)
The article was to development of Strengthening Qur'anic Character Values through Qur'an Reading Guidance (BBQ) Learning at MTs Al-Hikmah Bandar Lampung. The research method used is descriptive qualitative. This study employs descriptive data analysis techniques. Data were collected through interviews, observations, and documentation. The analysis was conducted descriptively to evaluate the effectiveness of BBQ learning in strengthening Qur'anic character values. The results of the study indicate that BBQ learning is highly effective in instilling Qur'anic character values, such as religiosity, honesty, discipline, and responsibility. This is evidenced by the successful application of the halaqah method, habituation, and exemplary behavior demonstrated by the teachers. Based on interviews and observations, this learning model has been proven to strengthen Qur'anic character in students. Challenges identified include low student motivation and limited facilities, which can be addressed through teacher support and a conducive learning environment. Based on the data obtained, BBQ learning is deemed highly suitable as a model for strengthening Qur'anic character values in madrasah students.